2011
DOI: 10.1371/journal.pone.0020590
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H: Quinone Oxidoreductase 1 Deficiency Conjoint with Marginal Vitamin C Deficiency Causes Cigarette Smoke Induced Myelodysplastic Syndromes

Abstract: BackgroundThe etiology of myelodysplastic syndromes (MDS) is largely unknown. Exposure to cigarette smoke (CS) is reported to be associated with MDS risk. There is inconsistent evidence that deficiency of NAD(P)H-quinone: oxidoreductase 1 (NQO1) increases the risk of MDS. Earlier we had shown that CS induces toxicity only in marginal vitamin C-deficient guinea pigs but not in vitamin C-sufficient ones. We therefore considered that NQO1 deficiency along with marginal vitamin C deficiency might produce MDS in CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In an epidemiologic study by Korte et al, approximately 10–50% of smoking-induced total leukemia mortality and up to 60% of smoking-related AML mortality were suggested to be related to benzene exposure [23]. Animal models have demonstrated that the deficiency of cytosolic protein NAD(P)H: quinone oxidoreductase-1 (NQO1) may be associated with myeloid pathology, such as myeloid hyperplasia [24,25]. Additionally, NQO1 deficiency in conjunction with vitamin C deficiency may be a risk factor for developing MDS [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an epidemiologic study by Korte et al, approximately 10–50% of smoking-induced total leukemia mortality and up to 60% of smoking-related AML mortality were suggested to be related to benzene exposure [23]. Animal models have demonstrated that the deficiency of cytosolic protein NAD(P)H: quinone oxidoreductase-1 (NQO1) may be associated with myeloid pathology, such as myeloid hyperplasia [24,25]. Additionally, NQO1 deficiency in conjunction with vitamin C deficiency may be a risk factor for developing MDS [25].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have demonstrated that the deficiency of cytosolic protein NAD(P)H: quinone oxidoreductase-1 (NQO1) may be associated with myeloid pathology, such as myeloid hyperplasia [24,25]. Additionally, NQO1 deficiency in conjunction with vitamin C deficiency may be a risk factor for developing MDS [25]. Recent analysis by Seastone et al [26] noted a greater number of molecular abnormalities in MDS patients, particularly related to histone modification highlighting potential tobacco-mediated molecular pathogenesis of MDS.…”
Section: Discussionmentioning
confidence: 99%
“…The putamen findings were highly consistent with the present study. There has also been a report of actual increase in the volume of the putamen in smokers [81]. However, there have also been reports of decreased gray matter [34] and increased white matter [36] in the putamen of smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The progression to disease is also likely to be associated with a deficiency in the detoxification system, such as the NAD(P)H:quinine oxidoreductase (NQO1) deficiency in the HSCs (Rothman et al, 1997). An experimental model of cigarette smoke exposure in guinea pigs demonstrated the correlation between NQO1 deficiency, cigarette smoke exposure, and progression to MDS (Das et al, 2011). Moreover, as noted in our discussion of senescence and autophagy, mice deficient for Atg7 progress to a myeloproliferative disorder/MDS (Mortensen et al, 2011).…”
Section: Ros In Mk Pathologymentioning
confidence: 99%